Patient and caregiver characteristics associated with caregiver burden in Parkinson’s disease: a palliative care approach - Macchi, Zachary A.; Koljack, Claire E.; Miyasaki, Janis M.; Katz, Maya; Galifianakis, Nick; Prizer, Lindsay P.; Sillau, Stefan H.; Kluger, Benzi M. (Annals of palliative medicine, 2020)
Parkinson's disease (PD) is a neurodegenerative disorder associated with caregiver burden. Higher rates of burden are associated with adverse outcomes for caregivers and patients. Our aim was to understand patient and caregiver predictors of caregiver burden in PD from a palliative care approach. We conducted a cross-sectional analysis of baseline data from PD patients and caregivers in a randomized trial of outpatient palliative care at three study sites: University of Colorado, University of Alberta, and University of California San Francisco. The primary outcome measure of caregiver burden, the Zarit Burden Interview (ZBI), was compared against the following patient and caregiver variables: site of care, age, disease/caretaking duration, presence of atypical parkinsonism, race, income, education level, deep brain stimulation status, the Unified Parkinson's Disease Rating Scale (UPDRS) and Edmonton Symptom Assessment System Revised: Parkinson Disease (ESAS) for symptom severity and burden, the Montreal Cognitive Assessment (MoCA) for cognitive function, Quality of Life in Alzheimer's Disease (QOL-AD) scale for patient and caregiver perspectives on patient general quality of life, Parkinson's Disease Questionnaire 39 (PDQ-39) scale for health-related quality of life, Hospital Anxiety and Depression Scale (HADS) for patient and caregiver mood, Prolonged Grief Questionnaire, Functional Assessment of Chronic Illness Therapy- Spiritual Well-Being (FACIT-SP) of patient and caregiver, and Palliative Performance Scale for functional status. A stepwise multivariate linear regression model was used to determine associations with ZBI. A total of 175 patients (70.9% male; average age 70.7±8.1 years; average disease duration 117.2±82.6 months), and 175 caregivers (73.1% female; average age 66.1±11.1 years) were included. Patient spiritual well-being (FACIT-SP Faith subscale, r2=0.024, P=0.0380), patient health-related quality of life (PDQ-39, r2=0.161, P<0.0001), caregiver depression (HADS Depression, r2=0.062, P=0.0014), caregiver anxiety (HADS Anxiety, r2=0.077, P=0.0002), and caregiver perspective on patient quality of life (QOL-AD Caregiver Perspective, r2=0.088, P<0.0001) were significant contributors to ZBI scores. Patient and caregiver factors contribute to caregiver burden in persons living with PD. These results suggest targets for future interventions to improve caregiver support.